Neoadjuvant B-RAF and MEK Inhibitor Targeted Therapy for Adult Papillary Craniopharyngiomas: A New Treatment Paradigm - Calvanese, Francesco; Jacquesson, Timothée; Manet, Romain; Vasiljevic, Alexandre; Lasolle, Hélène; Ducray, Francois; Raverot, Gerald; Jouanneau, Emmanuel (Frontiers in Endocrinology, 2022)
Background : Surgical and clinical management of craniopharyngiomas is associated with high long-term morbidity especially in the case of hypothalamic involvement. Improvements in knowledge of craniopharyngioma molecular biology may offer the possibility of safe and effective medical neoadjuvant treatments in a subset of patients harboring papillary subtype tumors with a BRAFV600E mutation. Method: We report herein two cases of tubero-infundibular and ventricular Papillary Craniopharyngiomas in which BRAF/MEK inhibitor combined therapy was used as adjuvant (Case 1) or neoadjuvant (Case 2) treatment, with a 90% reduction in tumor volume observed after only 5 months. In Case 2 the only surgical procedure used was a minimal invasive biopsy by the trans-ventricular neuroendoscopic approach. As a consequence, targeted therapy was administered in purely neoadjuvant fashion. After shrinkage of the tumor, both patients underwent fractionated radiotherapy on the small tumor remnant to achieve long-term tumor control. A review of a previously reported case has also been performed. Result: This approach led to tumor control with minimal long-term morbidity in both cases. No side effects or complications were reported after medical treatment and adjuvant radiotherapy. Conclusion: Our experience and a review of the literature argue for a change in the current treatment paradigm for Craniopharyngiomas (CPs). In giant and invasive tumors, confirmation of BRAFV600E mutated PCPs by biopsy and BRAF/MEK inhibitor therapy before proposing other treatments may be useful to improve long term outcomes for patients.